Oscillatory MHD Mixed Convection Boundary Layer Flow of Finite Dimension with Induced Pressure Gradient - S.K Ghosh (Journal of Applied Fluid Mechanics, 2016)
The purpose of present investigation is to deal with g-jitter forces of a time varing gravity field on unsteady hydromagnetic flow past a horizontal flat plate in the presence of a transverse magnetic field and the flow at the entrance also oscillates because of an applied pressue gradient. This problem deals with mixed convection driven by a combination of g-jitter and oscillating pressure gradient under the influence of an applied magnetic field. Analysis of this type find applications in space fluid system design and interpreting the experimental measurements in microgravity flow and heat transfer system.